Cryptogenic stroke in low-risk patients, consider a cardiac shunt at your peril. (19th July 2012) - Parry, Laura; Saeed, Saad Aldeen; Jaumdally, Rumi
Abstract : Patent foramen ovale (PFO) as a cause of cryptogenic stroke from paradoxical embolisation remains a controversial issue. The optimal care between medical and surgical management of these patients for the attending clinician remains a conundrum. We report a case of cryptogenic stroke in a woman aged 59, with a PFO, concomitant venous thrombosis and cryptogenic stroke. The case highlights the difficulty in diagnosing and managing such patients, particularly as recent evidence challenges the clinical practice of percutaneous closure and pathophysiological rationale.